2007
DOI: 10.1175/jas4001.1
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Polar Low Development on Baroclinicity and Physical Processes: An Idealized High-Resolution Numerical Experiment

Abstract: Polar low dynamics in an idealized atmosphere in which baroclinicity, stratification, and average temperature are varied in the typically observed range is investigated using a 5-km-resolution nonhydrostatic model. The baroclinicity is found to be the most important factor that strongly controls the polar low dynamics. When the baroclinicity is weak, a small, nearly axisymmetric vortex develops through a cooperative interaction between the vortex flow and cumulus convection. The surface friction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 49 publications
5
49
0
Order By: Relevance
“…The rest of the experiments focus on the relative influence of static stability N (N1), baroclinicity B (B1), and surface potential temperature θ s (θ 1) of the basic state on the formation and growth of a PL. Magnitudes of N, B and θ s prescribed for the CTL simulation are such that the conditions in the baroclinic channel are favourable for the formation of a PL (Sardie and Warner, 1983;Yanase and Niino, 2007). The reduction in the baroclinicity was achieved in the B1 simulation by weakening the vertical wind shear.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…The rest of the experiments focus on the relative influence of static stability N (N1), baroclinicity B (B1), and surface potential temperature θ s (θ 1) of the basic state on the formation and growth of a PL. Magnitudes of N, B and θ s prescribed for the CTL simulation are such that the conditions in the baroclinic channel are favourable for the formation of a PL (Sardie and Warner, 1983;Yanase and Niino, 2007). The reduction in the baroclinicity was achieved in the B1 simulation by weakening the vertical wind shear.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…On the other hand, Linders et al (2011) found a relatively weak response in sea-level pressure to SST variations of about -0.6 hPa K −1 . Apart from the differences in the model set-up, these widely varying results can be linked to the fact that several processes may operate simultaneously during the life cycle of a PL (Yanase and Niino, 2007). In the real atmosphere, the sensitivity of a PL to various conditions may vary from case to case depending on, for example, the dominating physical mechanism, geographical location, proximity of sea-ice, and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heating produces a positive anomaly of potential vorticity (PV) at low levels which contributes to the development of a warm core cyclone. Idealized numerical experiments (Yanase and Niino, 2007) have indicated that both diabatic heating due to convection and baroclinic instability have important roles in the development of polar lows. Yanase and Niino performed simulations on an initial vortex with diabatic heating and sea surface fluxes turned on and off and with different degrees of baroclinicity in the zonal flow.…”
Section: Introductionmentioning
confidence: 99%
“…Since Polar Lows usually form in cold air masses moving from cold continents or ice-covered regions over open water, this pattern of formation reflects mostly the geographically different sea surface temperature conditions. In a number of case studies it was demonstrated that Polar Lows can be described by dynamical high-resolution models [for the Japan Sea, see Fu et al (2004a), Yanase et al (2004), Yanase and Niino (2007); the Bering Sea see Bresch et al (1997); the Gulf of Alaska see Businger (1987) and Blier (1996)]. In all cases the model results were consistent with satellite observations.…”
Section: Present Knowledge: Mechanisms Regions and Case Studiesmentioning
confidence: 69%